1998
DOI: 10.1002/j.2168-9830.1998.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Freshman Engineering Courses*

Abstract: This study evaluates whether Purdue University's freshman engineering courses supply entering students with the necessary foundation to persist in engineering because of the skills they acquire in these courses. To measure this, we evaluate longitudinal data on retention and graduation rates of students that start in the standard first semester courses, start in the off‐sequence semester, or participate in our tutorial program. The study is based on historical data for the 28‐year period from 1966 through 1993. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
88
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 1 publication
4
88
0
Order By: Relevance
“…In addition to developing support programmes for struggling students and developing interventions to assist in the difficult transition from high school to college, this study advocated developing a means for gauging a student's motivation to persist as part of the engineering application process. In a study that analysed 15 years of data from one university, [16] analysis showed that of the 43% of students who left engineering, 84% did so before they moved from general engineering into a specific engineering department, which typically occurs in the sophomore year. Furthermore, Budny et al [16] showed that retention of these engineering students was related to GPA in the fall of the first year, a significant portion of which depends on performance in a first mathematics course.…”
Section: Relationship Between Engineering Retention and First Mathemamentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to developing support programmes for struggling students and developing interventions to assist in the difficult transition from high school to college, this study advocated developing a means for gauging a student's motivation to persist as part of the engineering application process. In a study that analysed 15 years of data from one university, [16] analysis showed that of the 43% of students who left engineering, 84% did so before they moved from general engineering into a specific engineering department, which typically occurs in the sophomore year. Furthermore, Budny et al [16] showed that retention of these engineering students was related to GPA in the fall of the first year, a significant portion of which depends on performance in a first mathematics course.…”
Section: Relationship Between Engineering Retention and First Mathemamentioning
confidence: 98%
“…In a study that analysed 15 years of data from one university, [16] analysis showed that of the 43% of students who left engineering, 84% did so before they moved from general engineering into a specific engineering department, which typically occurs in the sophomore year. Furthermore, Budny et al [16] showed that retention of these engineering students was related to GPA in the fall of the first year, a significant portion of which depends on performance in a first mathematics course. The data further showed that first-semester mathematics grades were an important predictor of retention in engineering, even if the mathematics course was a precalculus (remedial) course.…”
Section: Relationship Between Engineering Retention and First Mathemamentioning
confidence: 98%
“…ABET Engineering Criteria require that at least twenty-five percent of the credits for an engineering program be taken in mathematics and science courses, and some of the science courses for mechanical engineering curricula are expected to be in physics [1]. At least one study [2] has shown that success in the first mathematics course is useful in predicting persistence in an engineering program. While importance of mathematics and physics for success in studying engineering is unquestioned, deeper understanding of both how engineering faculty members expect their students to apply mathematics and physics and the extent to which engineering students are prepared to satisfy the expectations of their faculty members is required.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that nationally, approximately 50% of engineering and computer science students who begin their studies never graduate in those majors [3,4]. Underrepresented minority engineering students graduate at an estimated 33% [5].…”
Section: Introductionmentioning
confidence: 99%